Placenta Accreta Spectrum Disorder Complicated with Endometriosis: Systematic Review and Meta-Analysis - Matsuzaki, Shinya; Ueda, Yutaka; Nagase, Yoshikazu; Matsuzaki, Satoko; Kakuda, Mamoru; Kakuda, Sahori; Sakaguchi, Hitomi; Hisa, Tsuyoshi; Kamiura, Shoji (Biomedicines, 2022)
This study aimed to assess the relationship between placenta accreta spectrum disorder (PASD) and endometriosis. The relationships among pregnancy, assisted reproductive technology (ART), placenta previa, ART-conceived pregnancy and PASD were also determined. A systematic literature review was conducted using multiple computerized databases. Forty-eight studies (1990–2021) met the inclusion criteria. According to the adjusted pooled analysis (n = 3), endometriosis was associated with an increased prevalence of PASD (adjusted odds ratio [OR] 3.39, 95% confidence interval [CI] 1.96–5.87). In the included studies, the ART rate ranged from 18.2% to 37.2% for women with endometriosis. According to the adjusted pooled analysis, women who used ART were more likely to have placenta previa (n = 13: adjusted OR 2.96, 95%CI, 2.43–3.60) and PASD (n = 4: adjusted OR 3.54, 95%CI 1.86–6.76) than those who did not use ART. According to the sensitivity analysis using an unadjusted analysis accounting for the type of ART, frozen embryo transfer (ET) was associated with an increased risk of PASD (n = 4: OR 2.79, 95%CI, 1.22−6.37) compared to fresh ET. Endometriosis may be associated with an increased rate of PASD. Women with placenta previa complicated with endometriosis who conceived using frozen ET may be a high risk for PASD.